Association of plasma α-synuclein with cardiac 123I-MIBG scintigraphy in early Parkinson's disease. (23rd January 2022) - Park, Don Gueu; Kang, Juhee; An, Young-Sil; Chang, Jaerak; Yoon, Jung Han
Highlights: MIBG delayed H/M ratio positively correlated with plasma α-synuclein levels in PD. This correlation was independent with age, disease duration, and DAT availability. Striatal DAT uptake did not correlate with plasma α-synuclein levels. Plasma α-synuclein levels could be the marker of peripheral Lewy body deposition. Abstract: Cardiac 123 I-metaiodobenzylguanidine (MIBG) uptake correlates with the extent of cardiac sympathetic denervation found in disease with Lewy pathology, such as Parkinson's disease (PD). Protein α-synuclein, the main component of Lewy body, is a candidate biomarker of PD, but its relationship with cardiac MIBG uptake has never been explored. Plasma α-synuclein levels were measured in 37 patients with early PD. Cardiac 123 I-MIBG scintigraphy and 18 F-FP-CIT brain PET were performed, and striatal dopamine transporter (DAT) uptake was quantified using automated segmentation. The relationships of plasma α-synuclein levels with cardiac MIBG and striatal DAT uptake were investigated. The plasma α-synuclein level correlated with early (R = 0.38, P = 0.033) and delayed (R = 0.49, P = 0.0055) MIBG heart-to-mediastinum (H/M) ratios, and its correlation with delayed H/M ratio remained significant after adjustment with age, disease duration, motor severity, and striatal DAT uptake ( P = 0.016). The regional SUVRs of any subregions of caudate and putamen did not correlate with plasma α-synuclein level. In the patients with early PD, the plasma α-synuclein level correlated with cardiac sympathetic denervation, but not with nigrostriatal degeneration. This may suggest that plasma α-synuclein levels more readily reflect the peripheral deposition of Lewy bodies than their central deposition.